Leveraging 3D Printing Capability for Geopolymer Composites Based on Fly Ash with Cotton Fibers Addition - Barbara Kozub; Szymon Gądek; Bożena Tyliszczak; Leszek Wojnar; Kinga Korniejenko (International Journal of Engineering and Technology Innovation, 2024)
The study explores the use of fly ash as a base material for extrusion-based 3D printing and the impact of incorporating 1% cotton fibers on print properties. Characterization of the base material involves X-ray techniques, particle size distribution analysis, and microscopy. Mechanical properties are tested via bending and compressive strength. Meanwhile, thermal conductivity is also tested. Cotton fibers reduce print strength for loads applied perpendicularly and parallel to the printed sample layers by about 20-23% for compressive strength and 14-24% for flexural strength, possibly due to fiber agglomeration. Thermal conductivity decreases by approximately 12.17% compared to the base material. The results indicate the importance of the current study, i.e., assessing the different types of additives to enhance the mechanical and thermal properties of printed materials. Such ongoing research will facilitate the utilization of 3D printing in creating geopolymer composites.